Anemia in antenatal patients and its outcome: an experience in tertiary care centre - Ara, Shabnam; Saldanha, Cimona Lyn; Khan, Insha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Anemia is the most common hematological abnormality detected during the pregnancy and forms a major problem in affecting the females especially in the developing countries. Methods: All pregnant females with clinical evidence of anemia without any other co-morbidity attending the antenatal clinic were included in the study. Patients were studied in terms of the age, parity, inter-pregnancy spacing, type of pregnancy, post-partum outcome along with the biochemical tests like peripheral blood picture, hemoglobin estimation, and serum ferritin levels. Results: Total no. of patients was 500, age ≤20 years were 60 and ≥35 years were 107, mild anemia (10-10.9 gm%) 160, moderate anemia (7-10 gm%) 250, severe anemia (<7 gm%) 90. Normal vaginal delivery with medio-lateral episiotomy was done in 385 patients, normal vaginal delivery without medio-lateral episiotomy in 35 while lower-segment caesarean section in 80 patients. Pre-term delivery was done in 95 patients, post-term delivery in 20. 90 babies delivered were low-birth weight (<2500 gm), antepartum hemorrhage was seen in 10 patients while 20 patients had Post-partum hemorrhage. Conclusions: The present study concludes that anemia is still rampant in the society especially in pregnant women. The main cause of anemia-in-pregnancy is still the iron deficiency anemia. The peripheral blood picture, hemoglobin estimation, and serum ferritin levels form the basic pillars in the evaluation of the etiology and type of anemia. The multiple government sponsored facilities are to be made available to each pregnant female and that requires community, government as well as healthcare professional’s participation.